Disparities in who is asked about their perinatal mental health: an analysis of cross-sectional data from consecutive national maternity surveys - Harrison, S; Pilkington, V; Li, Y; Quigley, MA; Alderdice, F (BioMed Central, 2023)
Background The perinatal period is a vulnerable time, with one in five women experiencing mental health problems. Antenatal and postnatal appointments are key contact points for identifying women in need of support. Since 2014, the UK National Institute for Health and Care Excellence (NICE) has recommended that all women be asked about their mental health at their antenatal booking appointment and early in the postnatal period. The aim of this study was to assess the proportions of women who reported being asked about their mental health during the perinatal period across consecutive national maternity surveys (NMS) in England and to evaluate sociodemographic disparities in who was asked.